Principles of Tooth Preparation - Review Article - Ganesh Ramesh1 , Sanjna Nayar2 , S.Chandrakala3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Adequate tooth preparation is essential for the fit of fixed prosthodontics. Insufficient tooth preparationappears to be responsible for premature failures due to biological aspects, such as caries and endodonticor periodontal disease complications. The purpose of a fixed prosthodontic therapy may vary from therestoration of a single tooth to the rehabilitation of the complete occlusion. Successful preparations canbe obtained by systematically following these steps. It is important to critically evaluate each step beforeproceeding to the next step to ensure an optimal quality final restoration, which will serve the patient for along time.